Isolation and assessment of antibiotic resistance of Staphylococcus aureus in the air of an underground hard coal mines - Paśmionka, Iwona Beata; Cheluszka, Piotr; Gospodarek, Janina; Chmielowski, Krzysztof; Fries, Jiří (Scientific reports, 2025)
Mine aerosol poses a serious health threat due to its easy access to the human respiratory tract. Damage may be caused by the chemical composition of dust and the substances adsorbed on its surface, including microorganisms that potentially affect human health. Our proposed research aimed to isolate Staphylococcus aureus strains from coal mine bioaerosol and to assess its sensitivity towards selected antibiotics. Bioaerosol samples were collected in three underground hard coal mines located in Upper Silesia in southern Poland. Microbiological tests of the air samples were carried out according to standard microbiological techniques. All tested strains of Staphylococcus aureus were sensitive to oxacillin, which indicated the lack of methicillin-resistant isolates (MRSA) in the tested group. However, antibiotic resistance from macrolide and lincosamide groups was observed among certain strains. 10% of isolates were constitutive MLSB resistance, while 4% of strains were inductive MLSB resistance. Less than 1% of isolates were erythromycin-resistant and clindamycin-sensitive (MSB). Based on the Chi-square test, statistically significant differences were found in the frequency of MSB, MLSB inductive, and MLSB constitutive phenotypes. Almost 30% of the identified strains showed multi-antibiotic resistance. However, the Chi-square test did not reveal any statistically significant differences in the frequency of multidrug-resistant strains in the considered research areas. The analyses carried out constituted the first study related to the isolation and assessment of drug susceptibility of Staphylococcus aureus in the bioaerosol of hard coal mines. Identification of bioaerosol in underground coal mines is a key issue because, due to the presence of pathogens, it plays a significant role in limiting the spread of occupational diseases. For the health of miners, research into microbial communities benefits the promotion of microbiological control of mine air.
Keywords: mikrobiální testy citlivosti; Mining excavations; Polsko; mikrobiologie vzduchu; těžba uhlí; Drug sensitivity; lidé; Anti-Bacterial Agents; methicilin rezistentní Staphylococcus aureus; bakteriální léková rezistence; Air Microbiology; Staphylococcus aureus; Microbial Sensitivity Tests; Staphylococci; Respirable dust; Coal Mining; mnohočetná bakteriální léková rezistence; Bioaerosol; Drug Resistance, Multiple, Bacterial; Poland; antibakteriální látky; Drug Resistance, Bacterial; Methicillin-Resistant Staphylococcus aureus; Humans